Unusual genome expansion and transcription suppression in ectomycorrhizal Tricholoma matsutake by insertions of transposable elements. - Byoungnam Min; Hyeokjun Yoon; Julius Park; Youn-Lee Oh; Won-Sik Kong; Jong-Guk Kim; In-Geol Choi (PLoS ONE, 2020)
Genome sequencing of Tricholoma matsutake revealed its unusually large size as 189.0 Mbp, which is a consequence of extraordinarily high transposable element (TE) content. We identified that 702 genes were surrounded by TEs, and 83.2% of these genes were not transcribed at any developmental stage. This observation indicated that the insertion of TEs alters the transcription of the genes neighboring these TEs. Repeat-induced point mutation, such as C to T hypermutation with a bias over "CpG" dinucleotides, was also recognized in this genome, representing a typical defense mechanism against TEs during evolution. Many transcription factor genes were activated in both the primordia and fruiting body stages, which indicates that many regulatory processes are shared during the developmental stages. Small secreted protein genes (<300 aa) were dominantly transcribed in the hyphae, where symbiotic interactions occur with the hosts. Comparative analysis with 37 Agaricomycetes genomes revealed that IstB-like domains (PF01695) were conserved across taxonomically diverse mycorrhizal genomes, where the T. matsutake genome contained four copies of this domain. Three of the IstB-like genes were overexpressed in the hyphae. Similar to other ectomycorrhizal genomes, the CAZyme gene set was reduced in T. matsutake, including losses in the glycoside hydrolase genes. The T. matsutake genome sequence provides insight into the causes and consequences of genome size inflation.